Barium slag-based all-solid waste filling material and preparation method thereof

By comprehensively utilizing a variety of solid waste resources and combining microbial-induced mineralization technology, barium slag-based all solid waste filling materials are prepared, which solves the problems of low reuse of solid waste resources and unstable performance of filling materials, and achieves efficient and environmentally friendly resource recycling and performance improvement.

CN119841612APending Publication Date: 2025-04-18UNIV OF SCI & TECH BEIJING +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510063784.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and environmentally friendly to recycle and utilize solid waste resources such as barium slag and bacterial slag, resulting in low resource reuse and unstable filling material performance.

Method used

By comprehensively utilizing various solid waste resources such as barium slag, bacteria slag, desulfurization gypsum, ceramic waste powder, waste glass powder and steel slag, and combining microbial induced mineralization technology, barium slag-based all solid waste filling materials are prepared. The ratio and process of this material have been optimized, and Bacillus subtilis is added to generate calcium carbonate, improving the mechanical properties and stability of the material.

Benefits of technology

It realizes efficient reuse of solid waste resources such as barium slag, improves the mechanical properties and durability of filling materials, meets the application needs in mining, construction and road restoration, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005243646440000111
    Figure BDA0005243646440000111
Patent Text Reader

Abstract

The invention relates to the technical field of filling materials, and discloses a barium-slag-based all-solid-waste filling material and a preparation method thereof.The preparation method comprises the steps that barium slag is dried, smashed and then screened; drying the mushroom dregs at low temperature, and crushing until the particle size is less than 200 mu m; soaking the desulfurized gypsum in a 2% surfactant solution for 30 minutes, draining, and calcining at 150 DEG C for 2 hours; the method comprises the following steps: crushing waste glass until the particle size is 10-30 microns, magnetically separating to remove iron impurities, pickling to remove organic matters, and drying; heating the steel slag to 800 DEG C after water quenching, keeping the temperature for 2 hours, and crushing; mixing the barium slag, the mushroom dregs, the desulfurized gypsum, the ceramic waste powder, the glass powder and the steel slag according to a mass ratio; adding water and a toughening agent to obtain mixed slurry; and adding bacillus subtilis, stirring, adjusting the pH value to 8-9, and standing for 6-12 hours to finally obtain the barium slag-based all-solid waste filling material. Solid waste resources are utilized, the problem of solid waste treatment is solved, and meanwhile the filling material has good mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of filling materials, and in particular to a barium slag-based all-solid waste filling material and a preparation method thereof. Background Art

[0002] With the continuous advancement of industrialization, the large amount of solid waste has brought great pressure to the environment. In particular, the treatment and disposal of solid waste materials such as barium slag, steel slag, ceramic waste, waste glass and desulfurized gypsum have become environmental and resource issues that need to be solved urgently. Traditional solid waste treatment methods such as landfill and incineration not only pollute the environment, but also waste a lot of potential resources. At the same time, filling materials have a wide range of application needs in mining, construction, road repair and other fields. However, existing filling materials often face problems such as single source of raw materials, high cost and poor performance.

[0003] Barium slag is a waste product from certain industrial processes, and its chemical composition mainly includes barium oxide, silicon oxide, aluminum oxide, etc. Since its components have certain reactivity and structural characteristics, if they can be utilized through reasonable technical means, they can be prepared into a building or industrial filling material with good performance. However, the treatment and conversion of barium slag has always been a technical problem. Due to its complex structure, the composite utilization of barium slag and other wastes faces problems such as unstable performance, poor mechanical properties, and poor durability.

[0004] At the same time, as a byproduct of the fermentation industry, fungus residue has rich organic components and microbial activity, which has potential advantages in improving the mechanical properties and corrosion resistance of filling materials. However, due to its high water content and the fact that it usually requires specific treatment to achieve the best effect, the processing technology and stability are still technical bottlenecks when it is used in filling materials.

[0005] Therefore, how to efficiently and environmentally friendly recycle and utilize these solid waste resources, especially to improve the environmental friendliness of filling materials while ensuring their performance, is a key issue that needs to be urgently solved in the current technical field. Summary of the invention

[0006] In view of this, the present invention proposes a barium slag-based all-solid waste filling material and a preparation method thereof, aiming to solve the problem of efficient and environmentally friendly recycling and utilization of solid waste resources in current technology.

[0007] On the one hand, the present invention provides a barium slag-based all-solid waste filling material, comprising the following components in parts by weight:

[0008] 20-30 parts of barium slag, 30-40 parts of fungus slag, 15-25 parts of desulfurized gypsum, 10-15 parts of ceramic waste powder, 5-10 parts of glass powder and 5-10 parts of steel slag.

[0009] Furthermore, the barium slag comprises at least the following components in mass ratio:

[0010] The ratio of barium oxide: silicon oxide: aluminum oxide: calcium oxide: iron oxide is 25-35:30-35:3-4:15-25:5-10.

[0011] Furthermore, the fungus residue is a granular or powdery substance formed by drying and crushing the waste fungus bodies from industrial fermentation, and the fungus residue at least comprises: 20-30% protein and 10-20% carbohydrate.

[0012] Furthermore, the desulfurized gypsum comprises at least the following components in a mass ratio: calcium oxide: silicon oxide: iron oxide: magnesium oxide is 40-45: 1-2: 0-1: 0-1.

[0013] Furthermore, the particle size of the ceramic waste powder is less than 50 μm.

[0014] Furthermore, the glass powder is obtained by crushing, magnetic separation and acid washing of waste glass products, and the average particle size of the glass powder is 10-30 μm.

[0015] Furthermore, the steel slag is converter steel slag, and the steel slag includes the following components in mass ratio:

[0016] Calcium oxide: iron oxide %: magnesium oxide: silicon dioxide: aluminum oxide: manganese oxide: calcium sulfide is 30-50: 5-20: 5-15: 10-20: 2-8: 1-5: 0-3.

[0017] On the other hand, the present invention also provides a method for preparing the above-mentioned barium slag-based all-solid waste filling material, comprising:

[0018] The barium slag is dried to a moisture content of ≤2%, crushed and then sieved through a 100-mesh sieve;

[0019] The mushroom residue is dried naturally or at a low temperature of 40-50°C until the moisture content is ≤10%, and then crushed to a particle size of <200 μm;

[0020] Desulfurized gypsum was soaked in 2% surfactant solution for 30 min, filtered and dried, and then heated to 150°C and calcined for 2 h;

[0021] The waste glass products are crushed to a particle size of 10-30 μm, iron impurities are removed by a high gradient magnetic separator, the waste glass products are pickled by a 1-5% strong acid solution to remove organic impurities, and finally neutralized to neutrality and dried;

[0022] The slag is heated to 800-850°C and then added to room temperature water for water quenching, then heated to 800°C for 2 hours, cooled to room temperature and crushed to a particle size of <50μm;

[0023] Add 20-30 parts of barium slag, 30-40 parts of fungus slag, 15-25 parts of desulfurized gypsum, 10-15 parts of ceramic waste powder, 5-10 parts of glass powder and 5-10 parts of steel slag in a mixing device for mixing;

[0024] adding water to a mixing device at a water-to-solid ratio of 0.25, and adding a toughening agent to the mixing device to obtain a mixed slurry;

[0025] 1×10 7 CFU / mL of Bacillus subtilis is added into the mixing device at 5% of the total weight of the mixed slurry, and stirring is continued for 3-10 minutes;

[0026] At 25-30° C., the pH of the mixed slurry is adjusted to 8-9 by adding sodium carbonate, and the mixed slurry is kept standing for 6-12 hours to obtain a barium slag-based all-solid waste filling material.

[0027] Further, the mixed slurry is injected into a mold or used for on-site filling, cured in a natural environment for 48 hours, maintained at a temperature of 20-30° C. and a relative humidity of ≥50%, and demoulded after curing.

[0028] Furthermore, the toughening agent is waste rubber powder or plant fiber, and the added amount of the toughening agent is 1.5% of the total mass of the barium slag, fungus slag, desulfurized gypsum, ceramic waste powder, glass powder and steel slag.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention not only solves the environmental pollution problem of these wastes but also greatly improves the recycling rate of resources by comprehensively utilizing various solid waste resources such as barium slag, fungus slag, desulfurized gypsum, ceramic waste powder, waste glass powder and steel slag.

[0031] Through reasonable proportioning and optimized process, the prepared barium slag-based filling material has good mechanical properties and can meet the practical application needs in mining, construction and road repair. In particular, by introducing bacterial slag and microbial induced mineralization technology, the strength and stability of the filling material have been further improved. During the mineralization process, the calcium carbonate crystals generated enhance the performance of the filling material and significantly improve its service life.

[0032] Microbial induced mineralization technology is used to generate stable calcium carbonate crystals using microorganisms such as Bacillus subtilis, which further improves the structure and mechanical properties of the filling material without adding too many chemical additives. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] It should be noted that the main components of barium slag include barium oxide, silicon oxide, aluminum oxide, calcium oxide and iron oxide. It has certain reactivity and mineral structure, especially the components of barium oxide and silicon oxide can play a certain bonding role in the material.

[0035] effect:

[0036] Enhanced mechanical properties: The presence of calcium oxide and aluminum oxide in barium slag can enhance the hardness and compressive strength of the material and promote the structural stability of the material.

[0037] Providing mineral basis: The components such as barium oxide and silicon oxide in barium slag provide the mineral basis for the filling material, which can react with other components during the curing process to form a solid structure.

[0038] Improve corrosion resistance: Its unique chemical composition can effectively improve the corrosion resistance and durability of the filling material.

[0039] Mushroom residue is mainly composed of fermentation waste bacteria and contains a large amount of organic matter. The main components include protein, carbohydrates, fatty acids and trace minerals.

[0040] effect:

[0041] Enhance the toughness of materials: Fungus residue has good water absorption and flexibility, which can improve the toughness of filling materials and prevent brittle cracking of materials during construction and use.

[0042] Microbial induced mineralization: Bacterial slag can produce calcium carbonate by inducing mineralization, thereby improving the mechanical properties and durability of the filling material.

[0043] Improve corrosion resistance: The organic components in the fungus slag can effectively prevent the corrosion of the material in harsh environments and improve its long-term stability.

[0044] Desulfurization gypsum mainly contains calcium oxide, silicon oxide, iron oxide and a small amount of magnesium oxide.

[0045] effect:

[0046] Improve the hardness and strength of materials: The calcium oxide component of desulfurized gypsum can form a solid cement stone structure during the solidification process, thereby improving the compressive strength of the filling material.

[0047] Enhanced fire resistance: The presence of calcium oxide and silicon oxide makes the material have better high temperature resistance.

[0048] Improve density and water resistance: The density of gypsum can increase the water resistance of the filling material, prevent moisture penetration, and maintain the structural stability of the material.

[0049] Ceramic waste powder mainly contains mineral components such as silicon dioxide, aluminum oxide, calcium oxide, and iron oxide.

[0050] effect:

[0051] Increase the hardness and strength of materials: The silica and alumina in ceramic waste can significantly improve the hardness and compressive resistance of filling materials.

[0052] Promote mineral cross-linking reaction: The minerals in ceramic waste powder can react chemically with other components to promote the close integration of the internal structure of the material and enhance the overall stability of the material.

[0053] Improve the high temperature resistance of materials: The high melting point components of ceramic waste powder can increase the refractoriness and high temperature resistance of filling materials.

[0054] Glass powder is mainly composed of silicon dioxide, aluminum oxide, sodium oxide, calcium oxide and other ingredients.

[0055] effect:

[0056] Enhance the density of materials: Components such as silicon dioxide and calcium oxide in glass powder can improve the density of filling materials and reduce their porosity, thereby enhancing the strength and stability of the materials.

[0057] Provide additional mineral reaction sources: Silicates in glass powder can react with calcium components to further enhance the consolidation of the material.

[0058] Improved acid and alkali corrosion resistance: The glass component can improve the acid and alkali corrosion resistance of the filling material, making the material more durable in complex environments.

[0059] The main components of steel slag include calcium oxide, iron oxide, magnesium oxide, silicon dioxide, aluminum oxide and manganese oxide.

[0060] effect:

[0061] Enhance the compressive strength of materials: Calcium oxide and iron oxide in steel slag can improve the compressive strength of filling materials during the solidification process.

[0062] Improve the wear resistance of materials: The high hardness of steel slag particles helps to improve the wear resistance and damage resistance of filling materials.

[0063] Promote mineral reactions: Elements such as iron and magnesium in steel slag can react chemically with other components to improve the overall structural stability of the material.

[0064] It should be noted that the role of magnetic separation in removing impurities from waste glass is:

[0065] Preventing the influence of iron impurities on performance: Although other raw materials, such as barium slag or steel slag, may also contain iron components, the iron impurities in waste glass, such as iron nails and steel wires, are usually free iron substances and may be external pollutants. These iron impurities have a greater impact on the final material. The reasons are as follows:

[0066] Different participation in chemical reactions: Iron impurities in waste glass are different from iron in barium slag or iron in steel slag in chemical properties and reactivity. Iron impurities in waste glass may not form beneficial chemical reactions with other components, but exist as non-reactive impurities, affecting the homogeneity of the material.

[0067] Impact on physical properties: If the waste glass contains large iron impurities, they may cause the mechanical properties of the material to be unstable, such as easily causing local weaknesses, affecting the overall mechanical properties, especially in filling materials with high requirements for compressive and tensile properties.

[0068] Improve material stability: Removing iron impurities from waste glass can effectively prevent these impurities from forming unstable areas during the solidification process of the filling material, thereby improving the corrosion resistance, durability and stability of the filling material.

[0069] Reasons for the retention of iron components in steel slag and barium slag:

[0070] The iron components in barium slag and steel slag do not exist in a free form, but coexist with other components in the form of oxides, such as iron oxide. Moreover, these iron oxide components can often react favorably with other solid waste components, such as calcium and silicon, to enhance the strength and durability of the material.

[0071] The iron components in barium slag and steel slag have already participated in the formation of the chemical structure and network of the raw materials, so their retention contributes to the mechanical properties of the filling material. Unlike the free iron impurities in waste glass, the chemical behavior of these iron components is relatively stable.

[0072] It should be noted that for the pretreatment of steel slag: the water-quenched steel slag is placed in a furnace for heat treatment. This process is usually carried out at high temperature for a certain period of time, with the purpose of further transforming or solidifying the minerals in the steel slag. For example, some minerals may undergo dehydration or phase transformation, such as from garnet phase to calcium aluminum phase.

[0073] Pretreatment of desulfurized gypsum: Soak the desulfurized gypsum in a 2% surfactant solution to remove organic matter or water-soluble impurities that may be attached to the surface or inside of the desulfurized gypsum through the action of the surfactant. These impurities may affect the reactivity of the desulfurized gypsum or its compatibility with other ingredients.

[0074] The desulfurized gypsum is heated to 150°C and calcined. This process can improve the reactivity and stability of the desulfurized gypsum. At higher temperatures, the moisture and some harmful substances (such as chloride ions) in the desulfurized gypsum will be removed, giving it better physical and chemical properties. Calcination can increase the activity of the desulfurized gypsum, making it more suitable as a component of the filling material.

[0075] The technical solution of the present application will be described and explained in detail below in conjunction with embodiments.

[0076] Example 1

[0077] Raw materials and proportions:

[0078] Barium slag: 25 parts, wherein the mass ratio of effective components of barium oxide: silicon oxide: aluminum oxide: calcium oxide: iron oxide in the barium slag is 27:31:3:24:7.

[0079] Mushroom residue: 35 parts, the strain is Bacillus subtilis.

[0080] Desulfurized gypsum: 20 parts, wherein the mass ratio of the effective components calcium oxide: silicon oxide: iron oxide: magnesium oxide in the desulfurized gypsum is 43:1:0.7:0.4.

[0081] Ceramic waste powder: 12 parts

[0082] Glass powder: 8 parts

[0083] Steel slag: 5 parts, wherein the mass ratio of effective components in the steel slag, calcium oxide: iron oxide: magnesium oxide: silicon dioxide: aluminum oxide: manganese oxide: calcium sulfide, is 41:16:7:19:5:3:1.

[0084] Preparation steps:

[0085] Barium slag treatment: 25 parts of barium slag were heated in a dryer to a moisture content of 1.5%, then crushed by a pulverizer, and finally sieved through a 100-mesh sieve to obtain barium slag powder with uniform particle size.

[0086] Treatment of mushroom residue: 35 parts of mushroom residue were dried at low temperature (40-50° C.) until the moisture content was 7%, and then crushed to a particle size of less than 200 μm to form fine powder.

[0087] Desulfurized gypsum treatment: 20 parts of desulfurized gypsum were soaked in a 2% surfactant solution for 30 minutes, filtered and dried, and then heated to 150°C and calcined for 2 hours to obtain the treated desulfurized gypsum powder.

[0088] Treatment of ceramic waste powder: 12 parts of ceramic waste powder were crushed to ensure that the particle size was less than 50 μm.

[0089] Glass powder treatment: 8 parts of waste glass were crushed to a particle size of 10-30 μm, iron impurities were removed by a high gradient magnetic separator, and then pickled with a 1-5% strong acid solution to remove organic impurities, and finally neutralized to neutral and dried.

[0090] Steel slag treatment: 5 parts of steel slag were heated to 800-850°C and then added into room temperature water for water quenching. Subsequently, the slag was heated to 800°C and kept at a constant temperature for 2 hours. After cooling to room temperature, the slag was crushed to a particle size of <50 μm.

[0091] Mixing: Add barium slag, fungus slag, desulfurized gypsum, ceramic waste powder, glass powder and steel slag in a mass ratio (barium slag: 25 parts, fungus slag: 35 parts, desulfurized gypsum: 20 parts, ceramic waste powder: 12 parts, glass powder: 8 parts, steel slag: 5 parts) into a mixing equipment and mix thoroughly.

[0092] Adding water and toughening agent: Add water (water-to-solid ratio is 0.25) and waste rubber powder as a toughening agent (toughening agent ratio is 1.5%) to the mixture and mix well.

[0093] Inoculate Bacillus subtilis: 1×10 7 Bacillus subtilis at a CFU / mL level of 5% of the total weight of the mixed slurry is added to the mixing device and stirring is continued for 3-10 minutes.

[0094] Adjusting pH: The pH of the mixed slurry was adjusted to 8 by adding sodium carbonate and allowed to stand for 10 hours to promote the curing reaction.

[0095] Curing and demoulding: Inject the mixed slurry into the mold or directly use it for on-site filling. Keep it in a natural environment at 25-30℃ and relative humidity ≥50% for curing for 48 hours, demould it after curing, and obtain the hardened filling material.

[0096] Example 2 Raw materials and ratios:

[0097] Barium slag: 28 parts

[0098] Mushroom residue: 32 parts

[0099] Desulfurized gypsum: 18 parts

[0100] Ceramic waste powder: 12 parts

[0101] Glass powder: 6 parts

[0102] Steel slag: 4 parts

[0103] Preparation steps:

[0104] Barium slag treatment: The barium slag was treated in the same manner as in Example 1, i.e., dried to a moisture content of 2%, crushed and sieved.

[0105] Treatment of mushroom residue: The mushroom residue is dried at a low temperature of 40-50°C to a moisture content of 8%, and then crushed to a particle size of <200μm for treatment.

[0106] Desulfurized gypsum treatment: Desulfurized gypsum was treated according to the method of Example 1, including soaking, filtering and calcining.

[0107] Ceramic waste powder treatment:

[0108] The particle size of the ceramic waste powder is controlled to be less than 50 μm and then crushed.

[0109] Glass powder treatment: The glass powder is treated in the same manner as in Example 1, including crushing, magnetic separation, pickling and neutralization.

[0110] Slag treatment: The slag treatment was the same as in Example 1, by heating, quenching and crushing to a particle size of <50 μm.

[0111] Mixing: Mix 28 parts of barium slag, 32 parts of fungus slag, 18 parts of desulfurized gypsum, 12 parts of ceramic waste powder, 6 parts of glass powder and 4 parts of steel slag in proportion.

[0112] Adding water and toughening agent: Add water (water-to-solid ratio is 0.25) and plant fiber as toughening agent (toughening agent ratio is 1.5%) to the mixture and mix well.

[0113] Inoculation of Bacillus subtilis: Add Bacillus subtilis according to the method of Example 1 and stir evenly.

[0114] Adjust pH: Adjust pH to 8.5 by adding sodium carbonate and let stand for 10 hours to cure.

[0115] Curing and demoulding: Inject the mixed slurry into the mold or use it for on-site filling. Keep it in a natural environment at 25-30℃ and relative humidity ≥50% for 48 hours to cure, and then demould to obtain the filling material.

[0116] Example 3

[0117] Raw materials and proportions:

[0118] Barium slag: 22 parts

[0119] Mushroom residue: 38 portions

[0120] Desulfurized gypsum: 20 parts

[0121] Ceramic waste powder: 15 parts

[0122] Glass powder: 8 parts

[0123] Steel slag: 3 parts

[0124] Preparation steps:

[0125] Barium slag treatment: The barium slag treatment method is the same as the previous two embodiments, drying to a moisture content of 1.3%, crushing and screening.

[0126] Treatment of mushroom residue: The treatment of mushroom residue is the same as the previous example, drying at low temperature to a moisture content of 10%, and crushing to a particle size of <200μm.

[0127] Desulfurized gypsum treatment: Desulfurized gypsum is treated in the same steps as in the previous example.

[0128] Ceramic waste powder treatment: Ceramic waste powder particle size is less than 50μm and is crushed.

[0129] Glass powder treatment: The glass powder is treated in the same way as in the previous example, crushing, pickling and neutralization.

[0130] Slag treatment: The slag treatment is the same as the previous example, water quenching, heating to 800 ° C and then crushing to a particle size of <50 μm.

[0131] Mixing: Mix 22 parts of barium slag, 38 parts of fungus slag, 20 parts of desulfurized gypsum, 15 parts of ceramic waste powder, 8 parts of glass powder and 3 parts of steel slag in proportion.

[0132] Adding water and toughening agent: Add water (water-to-solid ratio of 0.25) and waste rubber powder as a toughening agent (toughening agent ratio of 1.5%) to the mixture and mix well.

[0133] Inoculation of Bacillus subtilis: Add Bacillus subtilis according to the method of Example 1 and continue stirring.

[0134] Adjust pH: Adjust pH to 8 by adding sodium carbonate and let stand for 10 hours.

[0135] Curing and demoulding: Inject the mixed slurry into the mold or fill it on site. Keep it at 25-30℃ and relative humidity ≥50% for 48 hours, and demould it after curing.

[0136] In Example 1, Example 2 and Example 3, the proportions of barium slag, fungus slag, desulfurized gypsum, ceramic waste powder, glass powder and steel slag are the same. The filling materials after demoulding in Examples 1-3 were sampled and tested for performance. Filling material samples were prepared according to GB17671-1999 "Test Method for Strength of Cement Mortar". The sample size was 30mm×30mm×50mm. The samples were cured at a temperature of 35°C and a humidity of more than 99.5%. The molded test blocks at different curing ages were tested according to the Chinese standard GB / T17671-1999 "Test Method for Cement - Strength Determination"

[0137] (MTCDS) tested the compressive strength, and the results are shown in Table 1.

[0138] Table 1 Compressive strength test results of filling materials

[0139]

[0140] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A barium slag-based all-solid waste filling material, characterized in that: The composition comprises the following components in parts by weight: 20-30 parts of barium slag, 30-40 parts of fungus slag, 15-25 parts of desulfurized gypsum, 10-15 parts of ceramic waste powder, 5-10 parts of glass powder and 5-10 parts of steel slag.

2. The barium slag-based all-solid waste filling material according to claim 1, characterized in that: The barium slag comprises at least the following components in mass ratio: The ratio of barium oxide: silicon oxide: aluminum oxide: calcium oxide: iron oxide is 25-35:30-35:3-4:15-25:5-10.

3. The barium slag-based all-solid waste filling material according to claim 1, characterized in that: The fungus residue is a granular or powdery substance formed by drying and crushing the waste fungus bodies from industrial fermentation. The fungus residue contains at least 20-30% protein and 10-20% carbohydrate.

4. The barium slag-based all-solid waste filling material according to claim 1, characterized in that: The desulfurized gypsum comprises at least the following components in a mass ratio: calcium oxide: silicon oxide: iron oxide: magnesium oxide of 40-45: 1-2: 0-1: 0-1.

5. The barium slag-based all-solid waste filling material according to claim 1, characterized in that: The particle size of the ceramic waste powder is less than 50 μm.

6. The barium slag-based all-solid waste filling material according to claim 1, characterized in that: The glass powder is obtained by crushing, magnetic separation and acid washing of waste glass products, and the average particle size of the glass powder is 10-30 μm.

7. The barium slag-based all-solid waste filling material according to claim 1, characterized in that: The steel slag is converter steel slag, and the steel slag includes the following components in mass ratio: Calcium oxide: iron oxide: magnesium oxide: silicon dioxide: aluminum oxide: manganese oxide: calcium sulfide is 30-50: 5-20: 5-15: 10-20: 2-8: 1-5: 0-3.

8. A method for preparing a barium slag-based all-solid waste filling material according to any one of claims 1 to 7, characterized in that: include: The barium slag is dried to a moisture content of ≤2%, crushed and then sieved through a 100-mesh sieve; The mushroom residue is dried naturally or at a low temperature of 40-50°C until the moisture content is ≤10%, and then crushed to a particle size of <200 μm; Desulfurized gypsum was soaked in 2% surfactant solution for 30 min, filtered and dried, and then heated to 150°C and calcined for 2 h; The waste glass products are crushed to a particle size of 10-30 μm, iron impurities are removed by a high gradient magnetic separator, the waste glass products are pickled by a 1-5% strong acid solution to remove organic impurities, and finally neutralized to neutrality and dried; The slag is heated to 800-850°C and then added to room temperature water for water quenching, then heated to 800°C for 2 hours, cooled to room temperature and crushed to a particle size of <50μm; Add 20-30 parts of barium slag, 30-40 parts of fungus slag, 15-25 parts of desulfurized gypsum, 10-15 parts of ceramic waste powder, 5-10 parts of glass powder and 5-10 parts of steel slag in a mixing device for mixing; adding water to a mixing device at a water-to-solid ratio of 0.25, and adding a toughening agent to the mixing device to obtain a mixed slurry; 1×10 7 CFU / mL of Bacillus subtilis is added into the mixing device at 5% of the total weight of the mixed slurry, and stirring is continued for 3-10 minutes; At 25-30° C., the pH of the mixed slurry is adjusted to 8-9 by adding sodium carbonate, and the mixed slurry is kept standing for 6-12 hours to obtain a barium slag-based all-solid waste filling material.

9. The method for preparing the barium slag-based all-solid waste filling material according to claim 8, characterized in that: Inject the mixed slurry into the mold or use it for on-site filling. Curing in the natural environment for 48 hours, maintaining the temperature at 20-30℃ and relative humidity ≥50%, and demoulding after curing.

10. The method for preparing the barium slag-based all-solid waste filling material according to claim 8, characterized in that: The toughening agent is waste rubber powder or plant fiber, and the added amount of the toughening agent is 1.5% of the total mass of the barium slag, fungus slag, desulfurized gypsum, ceramic waste powder, glass powder and steel slag.

Citation Information

Cited By

  • Low-cost cement-clinker-free filling material containing barium slag as well as preparation method and application of low-cost cement-clinker-free filling material

    CN120794538A

  • Low-cost cement-free clinker-free filling material containing barium residue and preparation method and application thereof

    CN120794538B